ANALISIS PENDAPATAN PETANI PENGGARAP DENGAN AKAD MUZARA’AH DAN FAKTOR YANG MEMPENGARUHINYA - DENI LUBIS; IRA ROCH INDRAWATI (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". The agricultural sector is one of the main sources of income people in developing countries. The problems faced are reduction in the quantity of land resources and limited access to business services, especially in terms of capital. Muzara’ah is an alternative source of sharia-based financing, and has advantages in terms of capital repayment waivers. This study aimed to analyze the level of income muzara’ah results when compared to the level of household expenditure of Cimaranten farmer in the village, and analyzes the factors that influence the muzara’ah results. In addition, the commodities of this study are sweet potatoes and paddy. The method used is multiple linear regression analysis. The results showed that the average cultivated land area recently is 0.3 hectares. The land area has not been able to sufficient the household expenses of farmers, so the extent of wetland things that should be worked out to sufficient the expenditure of farm households is 0.56 hectares. Factors influencing the muzara’ah results is length of education, length of farming experience, the amount of working capital loans, and land area.